Controlled release of Clenbuterol from a hydroxyapatite carrier for the treatment of Alzheimer’s Disease - Yi-Wen Lin; Chih-Hsiang Fang; Ya-Jyun Liang; Ching-Yun Yang; Wei-Ting Kuo; Feng-Huei Lin (Biomaterials Research, 2023)
Abstract Background Alzheimer’s disease is a neurodegenerative disorder, and Aβ aggregation is considered to be the central process implicated in its pathogenesis. Current treatments are faced by challenges such as serious side effects and reduced drug bioavailability. In this study, we developed a drug delivery system for intramuscular injection that uses cellular activity to achieve constant and long-term drug release. Methods Synthesized mesoporous hydroxyapatite (SHAP) was prepared via co-precipitation, and hydrophobic surface modification using stearic acid was then used to load clenbuterol by physical absorption, thus creating the drug delivery system. Clenbuterol release was achieved through cellular activity, with macrophage uptake triggering lysosome/endosome disruption, cytoplasmic release, extracellular exocytosis, and subsequent systemic circulation. Results We found that clenbuterol-loaded SHAP enabled sustained release for more than 2 weeks and effectively modulated inflammation, reduced Aβ oligomer-induced toxicity, and prevented Aβ aggregation. Conclusions Our findings suggest that treatment with clenbuterol loaded in this SHAP delivery system could be a promising strategy for treating Alzheimer’s disease. Graphical Abstract